Effects of Knowing the Task's Duration on Soccer Players' Positioning and Pacing Behaviour During Small-Sided Games - Ferraz, Ricardo (2020)
The study aimed to identify how the manipulation of knowledge regarding a training task duration constrains the pacing and tactical behaviour of soccer players when playing small-sided games (SSG). Twenty professional and experienced soccer players participated in a cross-sectional field study using three conditions: not informed on the duration of the SSG, which ended after 20 min (Unknown Condition); briefed about playing the SSG for 10 min, but after they completed the 10-min game, they were requested to complete another 10 min (Partial Condition) and informed before that they would play for 20 min (Known Condition). A global positioning system was used to measure the total distance covered and distances of different exercise training zones (walking to sprinting) and to access the dynamic players positioning through the distance from each player to all the teammates and opponents. Additionally, approximate entropy was measured to identify the regularity pattern of each gathered individual variable. The results indicate that the first 10 min of each scenario presented a higher physical impact independently of the initial information. During this time, the tactical behaviour also revealed higher variability. An increase in the distance of the teammates during the second period of 10-min for the Known scenario was also found, which may result from a lower pacing strategy. This study showed that the prior knowledge of the task duration led to different physical and tactical behaviours of the players. Furthermore, the relationship between the physical impact and the regularity of team game patterns should be well analysed by the coach, because the physical impact may be harmful to the development of the collective organization of the team.